Simulasi Driller’s Method Sebagai Metode Penanganan Kick pada Operasi Pemboran Darat - Joko Susilo (Swara Patra, 2019)
Oil and gas drilling operations are activities that use high technology, high investment and high riskl. The success of a drilling operation much influenced by the success, speed and accuracy in handling problems in the drilling operation. Drilling problems handling is very dependent on the human competence of the drilling operations, therefore they are needed correct and appropriate knowledge. The drilling problem that most important to be addressed and handling with properly is "kick", if this problem cannot be handled will result in a bigger problem that is "Blow out". In this discussion, the author tries to provide knowledge about one of the methods used in handling the problem of kick, namely Driller's Method.